Context and Linkage. Reflections on Comparative Research and 'Internationalism' in Criminology - Vagg, Jon (The British journal of criminology, 1993)
Comparative criminology has recently become a growth area, with the publication of several major books.1 With this in mind, I would like to present an argument about the current concerns and possible future directions of comparative criminological research. The argument begins with a consideration of how far we can detach crime and criminal justice data from their social, political, and economic contexts. This is treated as a matter of whether bodies of prima facie comparable data can be seen as addressing similar issues, given the context from which they come. My thesis is that both in terms of the crimes we seek to understand, and the theories we use to address them, we need to think much more carefully about the kinds of linkages that can be made between various aspects of criminal activity in different societies, about the relevances we are prepared to entertain, and what they are likely to mean in the context of any individual society. When we consider comparative data in this light, the nature of the crime and criminal justice problems under investigation may change in rather important ways. Reflection on those changes might offer some new directions for what I have termed a more internationalist' criminology. The kinds of directions that might flow from such a re-orientation are illustrated towards the end of this paper, with an admittedly eclectic set of examples